Legislasi Peraturan Daerah Partisipatif - La Ode Muhammad Iman Abdi Anantomo Uke (Institut Agama Islam Negeri (IAIN) Kendari, 2016)
Local Regulation legislation is the constitutional mandate of Article 18 (6), which reads